Associations between physical activity, screen time, and friends’ socialnetwork in a sample of Greek-Cypriot primary school children - Loucaides, Constantinos A. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. This study aimed to examine: (1) associations between children’s physical activity, screen time, and their friends’respective behaviours, and (2) whether a child’s popularity is associated with his/her physical activity and screen time.Methods. Participants included 136 children (37.5% boys and 62.5% girls) with a mean age of 11.8 years. Children worea pedometer for four weekdays to assess physical activity and completed a diary relating to the time spent in three screentime activities. They also nominated three friends for school and out-of-school hours.Results. Bivariate associations between school physical activity and friends’ physical activity ranged from r = 0.27 (p < 0.05)to r = 0.47 (p < 0.05) and for the whole day from r = 0.27 (p < 0.05) to r = 0.40 (p < 0.001). At the multivariate level, boys’ andgirls’ physical activity was associated with the physical activity of their best friend, explaining 42% and 11%, respectively,of the variance for school, and 11% and 9% of the variance, respectively, for whole day physical activity. In the boys’ analyses,time per day playing electronic games was associated with the child’s popularity, explaining 42% of the variance.Conclusions. Children’s physical activity is associated with the physical activity of their best friends, while among boys,time playing electronic games is associated with their popularity. Targeting children’s friendship networks may help promotephysical activity for both boys and girls and may help reduce time spent on electronic games among boys.
Keywords: pedometer; screen time; popularity; friendship network